Real-world usage pattern, effectiveness and safety of oral tramadol/dexketoprofen trometamol fixed-dose combination in moderate-to-severe acute pain in Asia: a prospective, multicentre, observational study - Ankur Gupta; Suwimon Tangwiwat; Cesar Dimayuga; Kok Yuen Ho; Bibek Gyanwali; Edgar Michael Eufemio; Edwin Bernardo; Gopinathan Raju; Keen Wai Chong; Kritsadakorn Waithayayothin; Leonardo Ona; Marc Anthony L Castro; et al. (BMJ Open)
Objectives This study aims to determine the usage pattern, effectiveness and safety of oral tramadol 75 mg and dexketoprofen trometamol 25 mg fixed-dose combination (TRAM/DKP FDC) in the short-term treatment of moderate-to-severe acute pain in real-world clinical practice in Asia.Design Real-world, prospective, multicentre, observational, phase IV study.Setting 13 tertiary-care hospital sites across the Philippines, Thailand, Malaysia and Singapore.Participants Adult patients aged 18–80 years prescribed TRAM/DKP FDC for the short-term (up to 5 days) treatment of moderate-to-severe acute pain.Main outcome measures Primary endpoints were the proportion of patients prescribed TRAM/DKP FDC with different types of postsurgical and non-surgical treatments, and the average dosing frequency and duration of TRAM/DKP FDC treatment. Secondary endpoints were the proportion of patients achieving ≥30% pain reduction at 8 hours post the first dose (pain severity was assessed using the 11-point Numeric Pain Rating Scale); patient satisfaction at the end of treatment (based on a 5-point Patient Global Evaluation Scale (PGE)) and safety including the incidence of adverse drug reactions (ADRs).Results Among 599 patients (median age 44 years, 61.3% female) enrolled in this study, 68.61% (n=411) were postsurgical and 31.39% (n=188) were non-surgical patients. TRAM/DKP FDC was prescribed in a diverse group of postsurgical patients (eg, orthopaedic, general and cancer surgery) as well as in non-surgical conditions (eg, lower back pain and musculoskeletal pain). In the majority of patients, TRAM/DKP FDC was prescribed every 8 hours (65.94%) and for 5 days (78.80%). There was a significant reduction in pain intensity throughout the study and 65% of patients achieved ≥30% pain reduction from baseline at 8 hours post the first dose of TRAM/DKP FDC on day 1. 95.69% of patients were satisfied with the treatment (rated good, very good and excellent on the PGE scale). Overall, 13.9% of patients reported ADRs; most were mild to moderate in severity. The most common ADRs were nausea, vomiting and dizziness.Conclusion This study showed that TRAM/DKP FDC was used in diverse types of postsurgical and non-surgical patients in the real-world setting in Asia. It effectively reduced pain and was well tolerated with a high level of patient satisfaction.